2021
DOI: 10.1177/00031348211029870
|View full text |Cite
|
Sign up to set email alerts
|

Regional Population-Based Workforce Shortages in General Surgery by Practicing Surgeon and Resident Trainee

Abstract: Background The physician shortage in the United States (US) continues to become more apparent. We aimed to evaluate the relationship between the US physician distribution from 2012-2019 by specialty at the state/regional level relative to the corresponding population growth. Methods US matched residents and practicing physicians from 2012-2019 were extracted from the National Resident Matching Program and Association of American Medical College databases, respectively. Residents and practicing physicians were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, even between 2013 and 2019, TKA utilization increased at the slowest rate in the West. Previous studies have identified the West to have the greatest physician shortage which may be manifesting as an inability to keep up with TKA demand [ 24 , 25 ]. This hypothesis is supported by the fact that despite a decrease in TKA utilization, the number of TKAs per surgeon increased by over 10% in the West, which was a greater rate of increase than the Midwest and South.…”
Section: Discussionmentioning
confidence: 99%
“…However, even between 2013 and 2019, TKA utilization increased at the slowest rate in the West. Previous studies have identified the West to have the greatest physician shortage which may be manifesting as an inability to keep up with TKA demand [ 24 , 25 ]. This hypothesis is supported by the fact that despite a decrease in TKA utilization, the number of TKAs per surgeon increased by over 10% in the West, which was a greater rate of increase than the Midwest and South.…”
Section: Discussionmentioning
confidence: 99%
“…Staff requirements may be more flexible for a simple procedure than for a relatively complex procedure. In Taiwan and some other area, increasing concerns have been reported regarding the regulation of residents’ work hours ( 19 ); the decline in the number of residency applications to surgical departments has resulted in a shortage of efficient staff ( 20 - 22 ). Hence, the introduction of robotic arms to replace manpower is a direction worth considering.…”
Section: Discussionmentioning
confidence: 99%